2006
DOI: 10.1002/art.22275
|View full text |Cite
|
Sign up to set email alerts
|

The functional variant of the inhibitory Fcγ receptor IIb (CD32B) is associated with the rate of radiologic joint damage and dendritic cell function in rheumatoid arthritis

Abstract: This study is the first to show that a single genetic variant, the FCGR2B 695T>C polymorphism, is a critical determinant of disease severity in RA and radically changes DC behavior. Our results underscore the key role of DCs in the progression of RA and reveal FcgammaRIIb as an important potential therapeutic target in RA and other autoimmune conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
48
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 48 publications
(69 reference statements)
3
48
0
1
Order By: Relevance
“…Genetic variants of CD32B gene are reported to affect the expression and function of this receptor and be associated with select autoimmune conditions in both mice and humans (40)(41)(42). We cannot completely exclude the possibility that specific CD32B polymorphisms, known to affect CD32B expression, partially account for our observations in RA; however, the extremely low prevalence of these polymorphisms limits their potential influence on our findings (41,42).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Genetic variants of CD32B gene are reported to affect the expression and function of this receptor and be associated with select autoimmune conditions in both mice and humans (40)(41)(42). We cannot completely exclude the possibility that specific CD32B polymorphisms, known to affect CD32B expression, partially account for our observations in RA; however, the extremely low prevalence of these polymorphisms limits their potential influence on our findings (41,42).…”
Section: Discussionmentioning
confidence: 73%
“…We cannot completely exclude the possibility that specific CD32B polymorphisms, known to affect CD32B expression, partially account for our observations in RA; however, the extremely low prevalence of these polymorphisms limits their potential influence on our findings (41,42).…”
Section: Discussionmentioning
confidence: 79%
“…Treatment in vitro of both healthy donor and patient monocytes with IL-4 plus IL-10 led to increases in Fc␥RIIb expression and decreases in IgG-mediated cytokine production (45). It has also been shown that a Fc␥RIIb polymorphism that was less inhibitory could serve as a strong predictor of joint damage in rheumatoid arthritis patients (60).…”
Section: Discussionmentioning
confidence: 99%
“…The Fc RIIIa variant is less effective in IC binding, implicating impaired clearance of ICs might play a role in the pathogenesis of RA, similar to SLE [71]. A functional variant of the inhibitory Fc RIIb is associated with disease severity rather than susceptibility [72]. APCs from patients with this variant fail to develop an inhibitory phenotype upon IC binding, thereby stimulating pro-inflammatory immune responses and subsequent joint damage.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%